Researching User Experience Needs in The Context of E-Marketing on The Example of Banking Sector in Poland - Robert BALCERZYK; Szymon GĄSIOROWSKI (Communications of International Proceedings, 2021)
Research is the basis for creating new products and implementing business ideas. Thanks to research, we can avoid failure. It is also the basis of the User Experience process and frequent tools used in marketing. The research has been conducted using desk research based on Internet sources, a diagnostic survey, and corridor studies. The target group was young Poles aged between 18 and 26. The research was aimed at diagnosing banking services and describing the financial situation and young people’s needs. It turns out that researching needs can provide many valuable conclusions. One does not have to spend much money researching the market and getting to know their customers better. Nonetheless, one does need to know how to select and carry out such research.
Keywords: User Experience; Researching Needs; Quantitative Research; Qualitative Research; Data Analysis.